'You're what's wrong with me': Fish Tank, The Selfish Giant and the language of contemporary British social realism. (1st September 2014) - Nwonka, Clive James
Contemporary British social realism has rapidly gained critical adherents in mainstream film critique, with the 2009 film Fish Tank hailed as a triumphant demonstration of British political cinema. The 2013 film The Selfish Giant followed this trend, and both have been aggrandized as a concrete critique of social inequality and, in a similar vein to the films of Ken Loach, offer an insight into the destabilizing effects of living with marginalized social categories. However, this article contends that the representation of working-class characters in Fish Tank and The Selfish Giant can also be interpreted as a depoliticized form of British social realism that fails to effectively depict the scope of social inequality or critique current policies and problems. This article interrogates the critical responses that annex Fish Tank and the Selfish Giant with Loach's body of films and suggests that the texts form part of a broader trend of decontextualization in contemporary British social realism.